The future of continuous renal replacement therapy. Issue 6 (20th February 2021) - See, Emily; Ronco, Claudio; Bellomo, Rinaldo
Abstract: Over the last 40 years, acute renal replacement therapy (RRT) in the intensive care units (ICUs) of high‐income countries has transitioned from the predominant use of intermittent hemodialysis (and the much less common use of peritoneal dialysis) to the almost exclusive use of continuous renal replacement therapy (CRRT). Accordingly, CRRT has become the most common form of vital organ support delivered to critically ill patients. A series of clinical and technical advances has enabled the transformation of basic CRRT machines into highly sophisticated and customized devices. Recent work has focused on using evidence from clinical trials to enhance the application of CRRT with regard to timing of initiation, choice of modality, dose, and anticoagulation. However, many questions remain unanswered. Uncertainty surrounding volume control and the utility of strategies to minimize circulatory stress are key areas for future development. Advances in membrane technology, combination with other extracorporeal therapies, and personalization of CRRT delivery may provide additional benefit to certain subgroups. Development of quality metrics and use of data analytics to audit and benchmark could provide important insight into practice, while biofeedback and automated CRRT prescription could increase safety. In this review, we summarize the evolution of CRRT and highlight several future areas for development.